Speech discrimination and impedance audiometry in stapedectomized patients - Lalitha (Journal of All India Institute of Speech and Hearing)
Middle ear surgery for otosclerosis ha in the past been evaluated primarily in ternlS of pre-operative and post-operative pure tone result. The anlount of reduction in the air-bone gap by surgery has been used as an indicator of success. It has been only in the last few years that speech discrimination scores have been used in the evaluation of stapes surg· ry, primarily because speech discrimination was thought to be a cochlear function unaltered by the surgical restoration of ossjcular chain.